Comparative antioxidant activity and 1H NMR profiling of Mediterranean fruit products. (March 2015) - Rosa, Antonella; Atzeri, Angela; Deiana, Monica; Scano, Paola; Incani, Alessandra; Piras, Cristina; Cesare Marincola, Flaminia
Abstract: In this study the antioxidant activity of methanol extracts obtained from Mediterranean fruit products (prickly pear fruit jam and cream, myrtle berries jam, orange and mandarin-orange marmalades) was evaluated and compared in several in vitro models of oxidative stress. The compositional profile of methanol extracts (carbohydrates, organic acids, amino acids, and main phenolic compounds) was characterized by 1 H NMR spectroscopy and the total phenol content was estimated by the Folin–Ciocalteu procedure. All extracts showed protective effect against thermal-cholesterol degradation, strictly correlated to total phenols. Extracts from prickly pear cream and myrtle berries jam preserved liposomes from Cu 2 + -induced oxidation, inhibiting the reduction of polyunsaturated fatty acids and the increase of malondialdehyde. Extracts from prickly pear cream and citrus marmalades significantly reduced the reactive oxygen species generation induced by tert -butylhydroperoxide in Caco-2 cell culture. The results of this work qualify all tested Mediterranean fruit preserves as a good source of biologically active components with considerable antioxidant potential. Graphical abstract: Highlights: Methanol extracts were obtained from five commercial Mediterranean fruit products. Main components of jam/marmalade extracts were characterized by 1 H NMR spectroscopy. Extracts protected cholesterol/fatty acids from oxidative degradation. Extracts from citrus marmalades and prickly pear cream reduced cell oxidation. All tested fruit preserves showed antioxidant activity and health properties.